Advances in HIV and AIDS Control - Okware, Samuel (IntechOpen, 2018)
The HIV epidemic has had a significant and profound impact on the world and health resources. Considerable progress has been made in understanding the risks and drivers of the epidemic. Antiretroviral drugs have relieved human suffering and prolonged life. However, access to quality management needs to scale up and be made universal. This book discusses critical issues related to the treatment of HIV infection and related co-infections and challenges in adherence and discordancy. New vaccine approaches discussed may provide the ultimate solution for eradication. Sharing knowledge from various experts in medical and basic sciences improves the quality of care for this persistent global threat. This book discusses emerging advances in HIV-AIDS management to support strategies for control and elimination.